Association of Coronary Artery Atherosclerosis With Brain White Matter Hyperintensity. Issue 8 (18th May 2021) - Johansen, Michelle C.; Gottesman, Rebecca F.; Kral, Brian G.; Vaidya, Dhananjay; Yanek, Lisa R.; Becker, Lewis C.; Becker, Diane M.; Nyquist, Paul
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We aim to determine, in healthy high-risk adults, the association between subclinical coronary artery disease and white matter hyperintensity (WMH) volume and location, independent of atherosclerotic risk factors. Methods: Seven hundred eighty-two asymptomatic first-degree relatives of index cases with early-onset coronary artery disease (<60 years old) from GeneSTAR (Genetic Study of Atherosclerosis Risk) with contemporaneous coronary computed tomography angiography and brain magnetic resonance imaging were analyzed. Multilevel mixed-effects linear regression models, accounting for family structure, evaluated the association of total WMH volume and 3 regions (deep WMH, periventricular WMH [PVWMH], or borderzone [cuff]) with markers of coronary artery disease. Separate models were created for total WMH, deep WMH, PVWMH, and cuff volumes, each, as dependent variables, across coronary computed tomography angiography variables, adjusted for covariates. Results: Mean age was 51 years ±10, with 58% women and 39% African American people. Participants with any coronary plaque had 52% larger WMH volumes than those without plaque (95% CI, 0.24–0.59). Per 1% greater coronary plaque volume, total WMH volumes were 0.07% larger (95% CI, 0.04–0.10). Every 1% higher total coronary plaque volume was associated with 5.03% larger deep WMH volume (95% CI, 4.67–5.38), 5.10% PVWMH larger volume (95% CI, 4.72–5.48), and 2.74% larger cuff volume (95% CI, 2.38–3.09) with differences in this association when comparing deep WMH to PVWMH ( P interaction, 0.001) or cuff ( P interaction, <0.001), respectively. Conclusions: In healthy, high-risk individuals, the presence and volume of coronary artery plaque are associated with larger WMH volumes, appearing the strongest for PVWMH. These findings in high-risk families suggest a disease relationship in 2 different vascular beds, beyond traditional risk factors, possibly due to genetic predisposition.